THE EFFECT OF EMOTIONAL INTELLIGENCE AND PARTICIPATORY PROCEDURAL JUSTICE ON JOB SATISFACTION - Fauzi, Haris; Juniarti, Atty (Jurnal Riset Bisnis dan Manajemen, 2023)
Human resources are the main production factor for organizations to achieve planned goals. Job satisfaction is important because in an organization employees are most dominant as a determinant of organizational success, this is due to high satisfaction being able to create a pleasant atmosphere so that employees are encouraged to excel in their organization. This study aims to determine the effect of participatory emotional intelligence and procedural justice on employee job satisfaction. In this study apply descriptive and verification methods. The population is all employees with a sample of 60 people selected through saturated sampling. testing with validity test and reliability test. Researchers used multiple linear regression and hypothesis testing with partial tests. This study found that emotional intelligence can have a significant positive effect on job satisfaction, and participatory procedural justice has a significant positive effect on job satisfaction.